A Non‐pathogenic Recombinant Leishmania Expressing Lipophosphoglycan 3 Against Experimental Infection with Leishmania infantum. (July 2017) - Pirdel, L.; Farajnia, S.
Abstract: Visceral leishmaniasis (VL) is caused by Leishmania infantum in the Mediterranean basin and affects primarily children and immunosuppressed individuals. Various strategies of vaccination have so far been examined by either protein or DNA without achievable complete protection against the disease. The live non‐pathogenic lizard parasite, Leishmania tarentolae, expressing elected Leishmania antigens has recently provided a promising new approach as a safe and effective live vaccine candidate to prevent leishmaniasis. Here, we evaluated the immunoprotective potential of a live recombinant L. tarentolae expressing Lipophosphoglycan 3 (LPG3) antigen against L. infantum infection in BALB/c mice. Results indicated that the administration of live recombinant Leishmania produced a significant high level of IFN‐ γ accompanied by reduced levels of IL‐10 as compared to wild‐type parasites as live vaccine control, thus suggesting the induction of a Th1‐type immune response in a mouse model of visceral leishmaniasis. Analysis of the IgG antibody response also showed high levels of IgG2a relative to IgG1 in sera of mice immunized with recombinant Leishmania parasites. However, immune responses elicited by this live vaccine conferred partial protection against infectious challenge. Therefore, further studies are required to increase its protective efficacy.